Four propellers submarine drone modelling in a real environment - Mohamed Moustanir; Karim Benkirane; Adil Sayouti; Hicham Medromi (Institute of Advanced Engineering and Science, 2021)
In order to reduce the hydrodynamic dampers and mechanical elements as rudders, we have in our previous publications proposed our architectural solution of an ROV with only four thrusters without rudders or diving bars. In the results we have justified the choice of the arrangement of the thrusters. Also, we have started the kinematic and dynamic studies of the marine robot and we have especially demonstrated by using the mathematical model under MATLAB in the last publication, that this ROV can move in a perfect environment without gravity or hydrodynamic dampers. In this article, we will study the behavior of this marine vehicle in a real environment with gravity and hydrodynamic dampers and we will view if this architectural solution can really allow the ROV to move and execute the given directional instructions.